Evaluation of Permit-to-Work System for Confined Spaces Using Value Stream Mapping and Root Cause Analysis - Aulia Nadia Rachmat; Nurul Ramadhanti; Arief Subekti; Adistia Puji Pramesti (Universitas Islam Raden Rahmat, Malang, 2026)
The work permit system fulfills clause 6.1.5 in PP No. 50 of 2012 concerning Occupational Health and Safety Management Systems (SMK3) and is required for high-risk activities, such as hot work, confined space operations, work at height, and scaffolding operations. This research aims to analyze waste in the confined space work permit issuance process and determined the root causes. The methods employed are Value Stream Mapping (VSM), to map the permit issuance workflow and identify existing waste. Root Cause Analysis (RCA), to analyze the root causes of waste. The results illustrate process efficiency of the confined space permit issuance process through Future State Mapping and recommendations for potential improvements to reduce waste permit issuance process, prevent work delays and avoiding impediments to company productivity. The waste analysis results of the confined space permit issuance process using Value Stream Mapping (VSM) indicate that the Approval 1 stage is already categorized as Lean Enterprise, with a Process Cycle Efficiency (PCE) value > 30%. However, the Approval 2 and Approval 3 stages are still classified as Un-Lean Enterprise, with PCE values < 30%. Recommended improvements include developing a notification-based website system, prioritizing new permit submissions, enabling mobile approvals, refining the permit issuance SOP and online submission process.